2011
DOI: 10.1007/s10886-011-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation, Conflict, and the Evolution of Queen Pheromones

Abstract: While chemical communication regulates individual behavior in a wide variety of species, these communication systems are most elaborated in insect societies. In these complex systems, pheromones produced by the reproductive individuals (queens) are critical in establishing and maintaining dominant reproductive status over hundreds to thousands of workers. The proximate and ultimate mechanisms by which these intricate pheromone communication systems evolved are largely unknown, though there has been much debate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
121
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 152 publications
(129 reference statements)
2
121
1
1
Order By: Relevance
“…Specific compounds that are characteristic for queens (queen pheromones) have been identified in various species [54,77,78]. However, our study is one of a few that revealed systematic chemical differences between castes across multiple species.…”
Section: Discussionmentioning
confidence: 86%
“…Specific compounds that are characteristic for queens (queen pheromones) have been identified in various species [54,77,78]. However, our study is one of a few that revealed systematic chemical differences between castes across multiple species.…”
Section: Discussionmentioning
confidence: 86%
“…4, Table 2; Smith et al, 2014). Many studies of social insect fertility signals have noted potential homologies with the contact sex pheromones of females of solitary insect species Kocher and Grozinger, 2011;Van Oystaeyen et al, 2014;Oi et al, 2015). Indeed, sex-based differences in the cuticular chemical profiles of males and females are the basis for short-range mate recognition for many solitary insects (Tregenza and Wedell, 1997;Ferveur and Cobb, 2010;Ginzel, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sexually dimorphic cuticular chemical profiles are thought to be the ancestral condition from which eusocial queen signals evolved, because of their widespread use as sex-specific mate recognition signals in solitary insects, including solitary and primitively eusocial Hymenoptera (Paulmier et al, 1999;Ayasse et al, 2001;Liebig et al, 2009;Kocher and Grozinger, 2011;Van Oystaeyen et al, 2014;Oi et al, 2015). Further investigation of the hydrocarbon patterns of males relative to those of female castes may prove essential in understanding the evolution of chemical signaling in social insects.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, because queen supersedure has become increasingly problematic in commercial beekeeping operations [36][37][38], it remains a high priority to identify the causes of premature supersedure. Previous studies have reported differences in the chemical composition of the queen mandibular gland [52,[55][56][57][58] and the Dufour's gland [59] based on the queen's reproductive state and insemination quantity, therefore it would be very telling if there were significant differences in queen pheromones between queens raised in miticide-free versus miticideladen beeswax cups, and if so, to what degree workers inside the colony perceive these differences.…”
Section: Discussionmentioning
confidence: 99%